A comparative study to evaluate the efficiency of two different chemical solvents used in softening gutta-percha. (Mustansiria Dental Journal, 2018)
Conventional root canal treatment despite having a reported high success rate may not invariably lead to the desired healing response in clinical practice because of shortcoming in the treatment. Different criteria have been used to define success and failure; mostly dependent on both clinical and radio-graphic findings and therefore sometimes there is a need to re-treat the root canal treated teeth.This study was done on twenty single rooted teeth, which divided equally and randomly into two groups depending on the solvent used, the first group was tested with the use of chloroform and the second group was tested with the use of eucalyptol oil.The chloroform showed the lowest mean of penetration time and was more efficient in softening the gutta-percha than the eucalyptol oil.Chloroform softened gutta-percha and ZOE sealer more statistically efficient than the eucalyptol oil.